Application of Magnetically Assisted Reactors for Modulation of Growth and Pyocyanin Production by Pseudomonas aeruginosa - Jabłońska, Joanna; Dubrowska, Kamila; Augustyniak, Adrian; Kordas, Marian; Rakoczy, Rafał (Frontiers in Bioengineering and Biotechnology, 2022)
Pseudomonas aeruginosa is a producer of desired secondary metabolites, including pyocyanin. Potential uses of this pigment urge a search for improved production methods. Recent trends in bioprocessing show the potential of the use of electromagnetic fields (EMFs) to influence the growth of microorganisms and even modulate the concentration of bioproducts. Here, we aimed at assessing the influence of rotating magnetic field (RMF) and static magnetic field (SMF) on pyocyanin production, growth rate, and respiration of P. aeruginosa. Moreover, exposure time to EMFs (2, 6, and 12 hours) and culture volume (10 mL and 50 mL) were initially assessed. P. aeruginosa was cultivated in magnetically assisted reactors with 5 and 50 Hz RMF (magnetic induction of 24.32 mT and 42.64 mT, respectively) and SMF (-17.37 mT). Growth kinetics was assessed with Gompertz equation. The viability was tested using resazurin assay, whereas pyocyanin production by chloroform-HCl methodology. The growth of P. aeruginosa was slightly stimulated by exposure to a RMF with 50 Hz (108% related to the control) and significantly by SMF (132% related to the control), while RMF 5Hz exposure prolonged the time of inflection (in comparison to RMF 50Hz and SMF). The 6-hour exposure to EMFs resulted in the highest pyocyanin production in comparison to the control, indicating a relationship between exposure time and product concentration. Moreover, cultures led in smaller volumes produced more pyocyanin. Our findings show that the use of different EMF types, frequency, and exposition time and volume could be used interchangeably to obtain different bioprocess aims.